From global to grassroots : the European Union, transnational advocacy, and combating violence against women - Montoya, Celeste (Oxford studies in gender and international relations., 2013)
This examination of the European Union and efforts to combat violence against women provides an empirical feminist analysis of the transnational strategies and processes that connect global and grassroots advocacy efforts. It looks beyond policy rhetoric to examine the extent to which this important human rights issue is being addressed.